Hyperspectral absorption coefficient measurements during the cruise HE503 with RV HEINCKE - Jochen Wollschläger; Beke Tietjen; Daniela Voß; Oliver Zielinski (PANGAEA, 2021)
This dataset was collected during the cruise HE503 (22.02.2018 - 01.03.2018) with RV HEINCKE from Bremerhaven, Germany to Bremerhaven, Germany. It contains absorption coefficients [m-1] from water constituents in a range of 400 to 710 nm (2 nm resolution). In total, 24 stations have been sampled. Where the water column was mixed, one sample was taken from approx. 5 m. In case of stratified water or chlorophyll-a maxima present, additional samples from greater depths were taken. The water samples were fractionated by filtration to investigate the absorption with respect to size classes. Thus, data from unfiltered samples are available as well as data from water that passed a 20 μm, 2 μm, and 0.2 μm filter, respectively (denoted as a_tot, a_20μm, a_2μm, and a_cdom). The absorption coefficient measurements were performed with a point-source integrating-cavity absorption meter (PSICAM) with a sample volume of approx. 400 ml. The specifications of the PSICAM, relevant publications, information regarding the measurements, calibration of the instrument, and data correction are provided in a separate document. Raw data are available on request from the authors. Chief Scientist of HE503: Dr. Thomas H. Badewien / Dr. Jochen Wollschläger , Institute for Chemistry and Biology of the Marine Environment (ICBM) Work related to Coastal ocean darkening - Light availability in the past and future marine environment (COD)